For the following system, use the second equation to make a substitution for y in the first equation is 2x + ( 2x – 3 ) = 5
Solution:
Given, two equations are 2x + y = 5 ⇒ ( 1 )
And y + 3 = 2x ⇒ ( 2 )
We have to find the solution of the given system of equations by substituting the y in second equation in the first equation.
Now, let us find the y value in the second equation
Then, eqn (2) ⇒ y + 3 = 2x
⇒ y = 2x – 3
Now, substitute the y value in ( 1 )
Eqn ( 1 ) ⇒ 2x + ( 2x – 3 ) = 5
⇒ 2x + 2x – 3 = 5
Thus we have used second equation to make a substitution for y in first equation
⇒ 4x = 5 + 3
⇒ 4x = 8
⇒ x = 2
Then, eqn 2 ⇒ y + 3 = 2(2)
⇒ y + 3 = 4
⇒ y = 1
Hence, the solution of the given system of equations is (2, 1).
By use the second equation to make a substitution for y in the first equation we get 2x + 2x – 3 = 5